Aboveground phytomass models for major species in shrub ecosystems of western Andalusia - Blanco Oyonarte, P.; Navarro Cerrillo, R. M. (Forest Systems, 2003)
This paper reports the first results of a project aimed at estimating aboveground biomass in shrub ecosystems of Western Andalusia. Models for predicting of dry phytomass (ms) from apparent biovolume (v) values were constructed by simple regression analysis, using shrub height, and maximum and minimum crown diameter as the specific data. Models obtained for the 31 selected species in these ecosystems were power, linear and logarithmic functions with determination coefficients (R2) between 0.751 and 0.989. The statistical significance of the results confirms the accuracy of the regional estimates provided by these models.